Challenge of Teaching Factory Based on School’s Potentials In West Java During Covid-19 Pandemic - et. al., Sintha Wahjusaputri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research explores the teaching factory implementation during the Covid-19 Pandemic and develops the teaching factory model framework. The teaching factory model framework is expected to improve SMK student's competency analytically and experimentally. This research uses a qualitative method consist of literature review, interview, and field survey. There are 6 (six) SMKs that is the object of this research, namely SMKN 9 Bandung, SMKN 11 Bandung, SMKN 1 Cipendeuy, SMKN 6 Garut, SMKN 1 Mundu, and SMKN 1 Pacet. This research shows that student competency can be improved through TF-6M training according to the industry needs, training for students and teachers through KKSI (Kamp Kreatif SMK Indonesia) using online learning, and facilities like laboratory or workshop that must be adjusted to Industry-standard (INDUKA). Furthermore, students' and teachers' professionalism can be obtained through the Professional Certification Test organized by INDUKA and SMKs. This research explained how the teaching factory's implementation based on School's potentials in West Java, Indonesia, in the face of the Covid-19 pandemic.